2017 XXXIInd General Assembly and Scientific Symposium of the International Union of Radio Science (URSI GASS) 2017
DOI: 10.23919/ursigass.2017.8105016
|View full text |Cite
|
Sign up to set email alerts
|

Risk based EMC for complex systems

Abstract: The rule-based approach, i.e. following electromagnetic interference standards, is the basic methodology assumed to result in electromagnetic compatible systems operating properly in their intended environment. For complex systems we need a smarter approach, based on assessing and controlling the electromagnetic risks. This risk-based approach is described, and applied to naval ships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 1 publication
(1 reference statement)
0
15
0
Order By: Relevance
“…Based on this case study, it can also be concluded that although standalone active devices have been EMC compliant, EMI issues could still occur when these active devices are inter-connected with passive devices [1] [5].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this case study, it can also be concluded that although standalone active devices have been EMC compliant, EMI issues could still occur when these active devices are inter-connected with passive devices [1] [5].…”
Section: Discussionmentioning
confidence: 99%
“…This matrix aims to track and assess possible sources and victims in a given environment. It has also been applied in naval ships with great success [18]. A model built upon the source-victim matrix concept and incorporating macro-scaled parameters is presented and discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…development processes struggle to keep up with technological evolution [1]. Moreover, the rising cost of certification and achieving full compliance in some industries such as maritime, along with accessible Commercial Off The Shelf (COTS) equipment that may not comply with maritime EMC standards [2], signals the need for a new approach. Therefore, a risk-based approach for EMC has been put forward as an alternative.…”
Section: Introductionmentioning
confidence: 99%